Faktor Risiko yang Berhubungan dengan Kejadian Hipertensi pada Pasien Rawat Inap di RSUD Sungai Dareh - Alfita Dewi; Eravianti, Eravianti; Welda Tulhusna (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
Based on data obtained from the Sungai Dareh Regional General Hospital in 2023, it was found that the number of hypertension sufferers in inpatient settings was 261 cases. Factors that influence hypertension are physical activity, diet and stress. The aim of this research is to determine the relationship between physical activity, diet and stress with the incidence of hypertension in inpatients at Sungai Dareh Regional Hospital in 2023. The type of research used is analytical by designcross sectional, which was carried out in April 2024. The population in this study was all 461 inpatients at Sungai Dareh Regional Hospital. Samples were taken by methodAccidental Sampling as many as 120 people. Data collection was carried out through direct interviews using a questionnaire. Then processed with SPSS and analyzed with statistical testsChi-squarewith a degree of significance (α= 0.05). The research results showed that 57.5% of patients had hypertension, 46.7% of patients had light physical activity, 55.8% of patients with poor diet, 58.3% of patients who experienced stress. Factors related to the incidence of hypertension are physical activity (p= 0.000), diet (p= 0.000), stress (p= 0.000). Based on the results of this research, it can be concluded that the independent variables (physical activity, diet, stress) are related to the dependent variable (Incidence of Hypertension). To minimize the incidence of hypertension, it is recommended that program holders increase the development of health promotion programs such as education and counseling for patients regarding the prevention of hypertension..